الإستراتيجيات الإتصالية للمنظمات عبر مواقع التواصل الإجتماعي في إدارة سمعتها: دراسة تطبيقية على شرطة دبي - طنطاوي، ميرهان محسن محمد السيد (الجمعية المصرية للعلاقات العامة, 2015)
أصبحت وسائل الإعلام الجديد أدوات متعددة للتفاعل بين المنظمات وجمهورها بشكل فعال ومستمر، ولعل هذا ما دعا المنظمات المختلفة سواء الحكومية أو الخاصة بدولة الإمارات العربية المتحدة لإنشاء حسابات لها عبر شبكات التواصل الاجتماعي لإدارة سمعتها بشكل أمثل خاصة في ظل التوجهات الحالية نحو الحكومة الذكية. تتمثل مشكلة الدراسة في التعرف على مدي استخدام المنظمات الحكومية (دراسة حالة للقيادة العامة لشرطة دبي) لشبكات التواصل الاجتماعي بالتطبيق على موقع التواصل الاجتماعي فيس في إدارة سمعتها، وتحليل طبيعة الاستراتيجيات الاتصالية التي تستخدمها المنظمة، والكيفية التي يتم من خلالها التفاعل مع الجماهير المتعاملة مع المنغمة عبر الأشكال الاتصالية المتنوعة الموجودة الحساب الخاص لشرطة دبي علي فيس بوك. وتنتمي هذه الدراسة إلى الدراسات الوصفية التي تسعى إلى رصد وتحليل وتوصيف الكيفية التي تم من خلالها توظيف موقع التواصل الاجتماعي فيس بوك لشرطة دبي كوسيلة لإدارة سمعتها، حيث تم رصد الحساب الخاص بشرطة دبي فيس بوك خلال الفترة من أكتوبر وحتى ديسمبر ٢٠١٤. اعتمدت الباحثة على أسلوب دراسة الحالة، والمقابلة المتعمقة مع القائمين على إدارة السمعة الإدارة العامة لشرطة دبي. كشفت أبرز نتائج الدراسة عن كون شرطة دبي استحدثت إدارة للسمعة بهدف تحقيق سمعة مميزة من خلال المعاملة الجيدة للجمهور، جودة الخدمات المقدمة والشفافية مع وسائل الإعلام المتنوعة وبناء جسور من الثقة، وهي القاعدة الذهبية لتطوير سمعة المنظمة عبر تحقق رضا وثقة الجمهور. أظهرت الدراسة تنوع وتعدد الاستراتيجيات الاتصالية التي توظفها شرطة دبي علي صفحتها فيس بوك لإدارة سمعتها.
New media has become a multi tools for interactions effectively and contentiously between corporates and their audiences, that’s why the government and private corporates in united Arab emirates create accounts on social networks to manage its reputation optimally especially in light of current trends toward smart government. This study aims to identify the extent of use governmental corporate (Dubai police) to social media networking, applied on social networking site Facebook in reputation management, this study also aims to analysis nature of the communicative strategies used by corporates, and the way of interaction with the audiences of corporates via diverse communications forms available on special account for the Dubai Police on Facebook. This study belongs to the descriptive studies that seek to monitor, analyze and characterize how they have been through the employment of social networking site Facebook Dubai Police as a means to manage its reputation, and the study is based on quantitative and qualitative approaches, where he was the special account at Dubai Police Facebook monitoring during the period from October to december 2014. Researcher relied on case study, in-depth interview with the existing reputation of the General Administration of Dubai Police Administration. It revealed the most prominent results of the study from the fact that the Dubai Police introduced a management reputation in order to achieve a distinctive reputation through good treatment to the public, the quality of services provided, and transparency with diverse media and to build bridges of trust, which is the golden rule to develop the reputation of the organization through the check satisfaction and public confidence. The study showed the diversity and multiplicity of resolv ability strategies employed by Dubai Police on the front page for Facebook to manage its reputation.
Keywords: وسائل الإتصالات -- مواقع التواصل الإجتماعي -- التخطيط الإستراتيجي -- الإستراتيجيات الإتصالية -- شرطة دبي -- الإمارات -- وسائل الإعلام -- المنظمات الحكومية